Effi ciency of allogenic platelet-rich plasmsa, combined with collagen, in rat's humerus injury healing - A. Yu. Vaza; M. S. Makarov; V. V. Slastinin; N. V. Borovkova; I. Yu. Klyukvin; D. Yu. Pokhitonov; I. N. Ponomarev (Трансплантология (Москва))
In experiment we studied influence of collagen, filled with platelet-rich plasma (PRP), on rats' bone regeneration in distal humerus. Used dose of PRP contained 130–135 pg/ml platelet-derived growth factor (PDGF). According to this level of PDGF, PRP-collagen treatment rapidly enhanced trabecular bones' growth, stimu-lated angiogenesis and reduced intensity of inflammation. Allogenic PRP, addressed to all experimental animals, allowed to make humerus healing 2 times shorter.